2017
DOI: 10.4103/ijcm.ijcm_30_16
|View full text |Cite
|
Sign up to set email alerts
|

A ten year audit of maternal mortality: Millennium development still a distant goal

Abstract: Objective:To assess various causes of maternal mortality over a ten year periodDesign:Retrospective audit of hospital case recordsSetting:Tertiary care hospitalPopulation:Pregnant women who expired in the premises of GTB Hospital.Materials and Methods:A retrospective audit of case records of maternal deaths was conducted for a ten year period (January 2005 to December 2014).Results:There were a total of 647 maternal deaths out of 1,16,641 live births. Sixty-eight percent (n = 445) of women were aged 21-30 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 14 publications
(18 reference statements)
5
20
0
Order By: Relevance
“…Anaemia has been identified as an important indirect cause of mortality. [ 24 ] Although antenatal anemia was not recorded in this study, severe anaemia in the peri-operative period was associated with a high mortality index. In contrast to other studies, mortality in obstetric patients with cardiac disease was low in our study.…”
Section: Discussionmentioning
confidence: 85%
“…Anaemia has been identified as an important indirect cause of mortality. [ 24 ] Although antenatal anemia was not recorded in this study, severe anaemia in the peri-operative period was associated with a high mortality index. In contrast to other studies, mortality in obstetric patients with cardiac disease was low in our study.…”
Section: Discussionmentioning
confidence: 85%
“…Singla et al, in the 10 years audit of MD at a tertiary hospital in Delhi reported 24.4% of MD due to hypertensive diseases in pregnancy. 7 While Kaur et al in the 7 years Chandigarh based study found just 8.8% of MD caused by hypertensive disorders. 8 A FOGSI study found that hypertensive disorders (eclampsia and severe preeclampsia) remained as the leading cause in the east (34%) and the north (22%) zones of India.…”
Section: Discussionmentioning
confidence: 96%
“…10. Obstetric hemorrhage, pre-eclampsia with its complications and sepsis are most common causes of maternal mortality in India, while anemia is the commonest indirect cause for maternal mortality [13] . A timely transfusion can save the life in such situation.…”
Section: Discussionmentioning
confidence: 99%